(untitled) (Global Journal of Science Frontier Research, 2017)
In paleolimnology, downcore assemblages are taken to be representative of the plankton that were living at some moment in the past. To evaluate the fidelity of the deposited diatom assemblage to that of the living plankton, a twenty-year series of whole-water plankton samples was compared to surface-sediment diatoms. When standardized and pooled, the 81 quarterly plankton samples were composed of Aulacoseira (51%), Cyclostephanos and other discoid diatoms (28%), Asterionella (9%), and Fragilaria (8%). In the deposited assemblage, however, the rank of the two most-common taxa was reversed: Cyclostephanos+ outnumbered Aulacoseira (47 and 34%, respectively). Some littoral taxa were over-represented in sediments (e.g. Encyonema) while others were under-represented (e.g. Gyrosigma). The reasons for these differences appear unrelated to frustule dissolution, but may insteadrelate to sampling frequency, sampling depth, and lake-specific characteristics.